2022
DOI: 10.1177/10497323221089880
|View full text |Cite
|
Sign up to set email alerts
|

Shifting Social Norms and Adolescent Girls’ Access to Sexual and Reproductive Health Services and Information in a South African Township

Abstract: Despite policy on adolescent sexual and reproductive health (SRH) services and education, teen pregnancies remain common in South Africa. Social norms and cultural resistance are a well-documented challenge for SRH program implementation in South Africa, and beyond. To gain insight on the complex picture of adolescents’ access to SRH information and services in a peri-urban township, we explored this topic from a diversity of perspectives, carrying out 86 interviews to capture perceptions of adolescents, their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“… Chandra-Mouli et al (2019) argue that family and community strongly influence how social and gender norms empower or disempower girls in their health seeking behaviours. Furthermore, social and family sanctions ( Bicchieri and Mercier, 2014 ) can influence the balance of power between males and females, perpetuating gender norms that are contextually realized depending on age, reproductive life stage, life course and partner status ( Gillespie et al , 2022 ). For example, studies showed that normative decision making related to early marriage often occurs between senior family members for social or economic reasons, with no or limited involvement of the girl ( Santhya and Jejeebhoy, 2015 ; Udgiri 2017 ; Girls Not Brides n.d ).…”
Section: The Reproductive Health Of Girls In Lmicsmentioning
confidence: 99%
“… Chandra-Mouli et al (2019) argue that family and community strongly influence how social and gender norms empower or disempower girls in their health seeking behaviours. Furthermore, social and family sanctions ( Bicchieri and Mercier, 2014 ) can influence the balance of power between males and females, perpetuating gender norms that are contextually realized depending on age, reproductive life stage, life course and partner status ( Gillespie et al , 2022 ). For example, studies showed that normative decision making related to early marriage often occurs between senior family members for social or economic reasons, with no or limited involvement of the girl ( Santhya and Jejeebhoy, 2015 ; Udgiri 2017 ; Girls Not Brides n.d ).…”
Section: The Reproductive Health Of Girls In Lmicsmentioning
confidence: 99%
“…The South African Department of Health (2020) indicated that boys endure growing pressure to adhere to culturally prescribed gender norms beginning in adolescence. In the same vein, these norms can discourage adolescents, especially girls, from seeking information and services related to contraception, family planning, and sexually transmitted infections (Gillespie et al, 2022).…”
Section: Cultural Normsmentioning
confidence: 99%
“…Cultural taboos can prevent girls from seeking information about contraception or reproductive health (Erasmus et al, 2020;Gillespie et al, 2022), leading to uninformed decisions and potential health risks like early pregnancies or sexually transmitted infections. Likewise, girls might receive inadequate information due to cultural taboos (Meagley et al, 2016).…”
Section: Taboosmentioning
confidence: 99%